Analysis of antigen‐antibody cross‐reactivity among lineages and sublineages of Babesia microti parasites using human babesiosis specimens. Issue 5 (9th March 2018) - Sayama, Yusuke; Zamoto‐Niikura, Aya; Matsumoto, Chieko; Saijo, Masayuki; Ishihara, Chiaki; Matsubayashi, Keiji; Nagai, Tadashi; Satake, Masahiro
Abstract : BACKGROUND: Human babesiosis is caused mainly by Babesia microti and has recently become a public health concern due to an increase in transfusion‐transmitted infection. Thus, the development of an antibody detection method with high specificity and sensitivity is a priority. Seroreactivity against B. microti has been reported to be highly specific not only to B. microti lineages but also to sublineages. This study aimed to elucidate the human antibody reactivity against various lineages, including US, Kobe, and Hobetsu, and sublineages (North America and East Asia) in the US lineage. STUDY DESIGN AND METHODS: Twenty samples obtained from individuals infected with B. microti in the United States were tested for the presence of anti‐ B. microti antibodies using indirect immunofluorescence assay (IFA) and Western blotting (WB) to indicate antigens of each (sub‐)lineage. RESULTS: By IFA, 20 samples showed reactivity to the North America sublineage (titer range, 64‐4096), 16 to the East Asia sublineage (64‐512), 10 to the Kobe (64‐128), and five to the Hobetsu (64). Antibody titers to the East Asia sublineage, Kobe, and Hobetsu were significantly lower than those to the North America sublineage (p < 0.01). By WB, in parallel with the IFA results, 18 samples showed strong reactions to the North America sublineage, weak reactions to the East Asia sublineage, and near‐zero reactions to the Kobe and Hobetsu. CONCLUSION: Human antibodies induced by B. microti infection are highly specific against B. microti lineages and sublineages with low cross‐reactivity. Developing a precise antibody detection method may require specific antigens based on B. microti lineages and sublineages.